Can an Ageing Scotland Afford Independence? - Katerina Lisenkova; Marcel Mérette (European Regional Science Association (ERSA), 2014)
The aim and scope of this paper is to isolate the effects of population ageing in the context of potential Scottish independence. Fiscal challenges are often quoted as a strong argument against independence. Demographic processes play an important role in determining future economic growth via their impact on labour market, saving behaviour and government budget. One of the arguments that have been raised during the debate is that Scotland is in a worse demographic situation than RUK, and independence will make it harder for it to provide for its ageing population. In this paper we developed a multi-regional OLG-CGE model for Scotland, the rest of the UK (RUK) and the rest of the World (ROW). The model is used to evaluate the two scenarios: the status quo and the independence scenarios. The status quo scenario assumes that Scotland stays part of the UK and all government expenditures associated with its ageing population (mainly pensions and health) are funded on a UK-wide basis. In the independence scenario, Scotland and the rest of the UK have separate government budget constraints and pay for the growing demands of their ageing populations independently. According to the status quo scenario, population ageing has a strong impact on economic development in both regions. By 2060 output per person falls in Scotland and RUK by 9% and 10% respectively and total government spending increases by about 4 percentage points of GDP in both regions. To achieve government budget balance the effective labour income tax rate has to increase from about 13.0% to 21.5%. The comparison of the two scenarios suggests that Scotland is worse off in the case of independence. The effective labour income tax rate in the independence scenario has to increase further compared with the status quo scenario. The additional increase reaches its maximum in 2035 at 1.4 percentage points. The additional rise in the tax rate is non-negligible, but is much smaller than the population ageing effect (status quo scenario) which generates an increase of about 8.5 percentage points by 2060. The difference for government finances between the status quo and independence scenarios is thus relatively small. The bottom line is that, clearly, population ageing is a major issue for Scotland and RUK, no matter the final result of the independence vote. But unless the speed and intensity of population ageing in Scotland increases rapidly relative to RUK in the years to come, demographic change is not a strong argument to influence the choice between the status quo and independence.
Keywords: C68; E17; H53; J11; 330; Scotland; independence; OLG; government spending; population ageing